On the (*)-prime radical of a ring with involution - (:unkn) unknown (My University, 1999)
Bu çalışmada involusyon halkaları için şu sonuçlar elde edildi: 1) involusyon halkalarının ( asosyatif veya değil) (*)-asaI radikal, (*)-yarıasal ideal ve (*)-nilpotent ideal tanımları verildi, involusyon halkalarında (*)-asal radikaldir, tüm yarıasal ideallerin kesişiminin ve tüm (*)-nilpotent elemanların kümesinin aynı olduğu gösterildi. 2) involusyon halkalarında (*)-çözülebilir ideal tanımı verildi. Eğer bir involusyon halkasında (*)-ideallerin artan zincir koşulu sağlanırsa (*)-asal radikalinin (*)-çözülebilir olduğu gösterildi. 3) involusyon halkalarında sağ (sol) (*)-asal radikal tanımları verildi. Birimli, asosyatif bir involusyon halkası için, sağ (sol) (*)-asal radikalinin (*)-asal radikalle aynı olduğu gösterildi.

In this paper we have obtained the following results for a ring with involution: 1) For a ring (associative or non-associative) with involution we introduce definitions of a (*)- prime radical, a (*)-semiprime ideal and a (*)-nilpotent element. For any ring with involution the (*)- prime radical, the intersection of all (*)-semiprime ideals and the set of all (*)-nilpotent elements are equal. 2) For a ring with involution we introduce a definition of a (*)-solvable ideal. If a ring with involution satistles the ascending chain condition for (*)-ideaIs then its (*)-prime radical is (*)-solvable. 3) We introduce a definition of a right (left) (*)-prime radical of a ring with involution. For an associative (*)-ring with unity its right (left) (*)-prime radical is equal to the (*)-prime radical.
Involusyon halkalarının (*)-asal radikali üzerine